Comparing the Effectiveness of Ondansetron and Dexamethasone on Nausea/Vomiting in Cesarean Section under Spinal Anesthesia - Nida Shahid; Saira Jamshed; Farah Khan; Asim Masroor Rasheed; Akhtar Ali; Adnan Anwar (ziauddin University, 2024)
Background: Nausea and vomiting are frequently witnessed for pregnant women who undergo C-sections under spinal anesthesia. The objective of this study was to determine the effectiveness of Ondansetron and Dexamethasone on nausea and vomiting in patients undergoing spinal anesthesia for cesarean section. Methods: This was an experimental study conducted in the Department of Anesthesia and Department of Obstetrics and Gynecology, Hamdard University Hospital, from April 15, 2021-August 15, 2021. Pregnant women (n=93) with the age >18-<45 years with American Society of Anesthesiologists (ASA) class I and II were enrolled. Group-A (n=43) were given 8 mg of Ondansetron, while Group-B (n=50) received 8mg of Dexamethasone. Post-operative nausea and vomiting assessment was done by Apfel score and was measured at 1 minute, 5 minutes, 10 minutes and 30 minutes after spinal anesthesia. Chi-square and student t-tests were performed for analysis. Results: There was an insignificant difference (p=0.029) in terms of the demographic factors and vital signs between both the groups while a significant difference (p=0.05) was reported only in systolic blood pressure between both the groups. Insignificant difference was observed in parity, use of intraoperative opioids, sedatives, use of vasopressors, postoperative vomiting and shivering (p>0.05). Post-operative 11(22.0%) cases reported nausea and 1.0(2.0%) cases of vomiting in the dexamethasone group with significant difference (p=0.001), however, participants of the Ondansetron group did not report any symptom. Conclusion: Ondansetron 4mg/kg dose decreased the propensity of nausea and vomiting after cesarean section. However, dexamethasone 8mg/kg seemed to be effective in controlling postoperative vomiting only. Keywords: Nausea; Vomiting; Ondansetron; Dexamethasone; Spinal Anesthesia.